The Role Of Shareholders And Good Corporate Governance In Sharia Banks - Zulpahmi, Zulpahmi; Sumardi, Sumardi; Akmal, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2018)
ABSTRACTThe variables used in this research are the role of audit committee and internal audit as the dependent variables and the implementation of good corporate governance as the independent variable. This research employs a purposive sampling to determine the samples based on certain criteria and 3 (three) Sharia banks are obtained since they have met the pre-determined criteria. The primary data are obtained through questionnaires distributed to 43 employees of Audit Committee, Internal Auditor, and GCG as the respondents. This research employs a Multiple Linear Regression Analysis as its technical analysis. The results of this research show that the role of audit committee positively and significantly influences the implementation of good corporate governance. Keywords: Audit Committee, internal audit, implementation of Good Corporate Governance